Analisis Mekanisme Akad Rahn, Qardh dan Ijarah Pada Produk Pembiayaan Mitra Emas IB Maslahah: Studi Kasus Di BJB Syariah KCP Ciamis - Alya Khairunnisa; Joni Joni (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
Pawn included on one of the product financing in islamic banking. Bank BJB Syariah KCP Ciamis there is a product financing Gold Partner iB Maslahah. As known whether the mechanism of the contract that exists on the financing product Gold Partner iB Maslahah is in accordance with theory and existing regulations or not. The formulation of this research problem was how the mechanism akad rahn, qardh and finance on finance products Gold Partner iB Maslahah which is run by BJB Syariah KCP Ciamis. The method used in this research is descriptive method with qualitative approach. This study also uses two data sources, namely primary and secondary sources. The technique of data collection is done by observation, interview, and documentation. Data analysis techniques used are data reduction, data presentation, and clonclusioan drawing/verification. Based on the research results obtained the conclusion that the mechanism of akad rahn, qardh, and finance in the financing Gold Partner iB Maslahah that the mechanism of each contract already well underway, with a wide Gold Partner iB Maslahah itself can facilitate customers who wish to borrow money quickly and it takes time. In the process of redemption of any bank to do it carefully and in accordance with the operational standards that exist. The Bank does not give excess or deficiency in the funds of the loan given to the customer.